The splendid and the vile [large type] : a saga of Churchill, family, and defiance during the Blitz - Larson, Erik, 1954- (Random House Large Print, 2020)
Draws on personal diaries, archival documents and declassified intelligence in a portrait of Winston Churchill that explores his day-to-day experiences during the Blitz and his role in uniting England.